The end of the Last Glacial Maximum in the Iberian Peninsula characterized by the small-mammal assemblages - Bañuls-Cardona, S.; López-García, J.M.; Blain, H.-A.; Lozano-Fernández, I.; Cuenca-Bescós, G. (Journal of Iberian Geology, 2014)
This paper presents a palaeoenvironmental and palaeoclimatic approach to the end of the Last Glacial Maximum (LGM) in the Iberian Peninsula on the basis of the small-mammal assemblages (insectivores, bats and rodents). The LGM is an important period in our climate history defined by the maximum extension of ice sheets between ca. 22 and 19 ka BP. In the Mediterranean region the LGM is characterized by humid conditions, which allow for the development of arboreal vegetation. The small-mammal remains described in this study were recovered from four different sites within the Iberian Peninsula: El Mirón cave (Ramales de la Victoria, Cantabria), Valdavara-1 (Becerreá, Lugo), El Portalón (Sierra de Atapuerca, Burgos), and Sala de las Chimeneas (Maltravieso, Cáceres). We found in these sites a non-analogue association represented by species associated with mid-European climatic conditions, such as the voles Chionomys nivalis, Microtus arvalis, Microtus agrestis and Microtus oeconomus, together with species associated with Mediterranean requirements, such as Microtus (Iberomys) cabrerae and Microtus (Terricola) duodecimcostatus. These assemblages reveal that the climate was harsher than today in the sites under study, though not as rigorous as elsewhere in Europe, with mean annual temperatures lower than present and an environment dominated by wet open meadows. All our data have been compared with other environmental and climatic proxies, global isotope curves and pollen data, providing a scenario for the palaeoclimatic and palaeoenvironmental conditions that occurred during the LGM in the Iberian Peninsula.